Advancing professional teaching in South Africa: Lessons learnt from policy frameworks that have regulated teachers' work. - Rusznyak, L.; Kimathi, F. (2018)
Teaching and teacher education in South Africa have emerged from a highly fragmented past. Teachers from diverse backgrounds, experiences and qualifications find themselves working together in schools where they do not necessarily have access to a common language of practice, nor a shared understanding of professional teaching practices. To address these challenges, the South African Council of Educators (SACE) has developed a set of professional teaching standards for use in the South African context. This is not the first time a policy framework has tried to articulate and direct teachers’ work. This paper analyses four other frameworks that have been used to regulate, monitor and evaluate the work of South African teachers over the past two decades. These other frameworks are The Roles of the Educator and Their Associated Competences, the SACE Code of Professional Ethics, the Integrated Quality Management System (IQMS) and the Basic Competences of a Beginner Teacher. Our analysis shows how these frameworks present teaching in ways that constrain teacher professionalism in some ways. They address some aspects of professional teaching while ignoring others. In particular, none of them adequately acknowledge the relations between knowledge, skills, judgement and the ethical orientations that underpin professional teaching. The ways in which previous frameworks have constrained teacher professionalism has important implications for SACE if its set of professional teaching standards is to more successfully enhance teacher professionalism in the South African context.